2022
DOI: 10.17219/dmp/145593
|View full text |Cite
|
Sign up to set email alerts
|

Effect of non-surgical periodontal therapy on the salivary levels of omentin-1, a novel adipokine biomarker in periodontitis: A clinico-biochemical study

Abstract: Background. Biomarkers are emerging, advanced diagnostic tools for the assessment of periodontal disease progression. Omentin-1 is an anti-inflammatory adipocytokine, which has been observed and studied in the saliva of periodontitis patients. Non-surgical periodontal therapy (NSPT) is considered a vital part of periodontal disease treatment.Objectives. The study aimed to evaluate the interventional effect of NSPT on the levels of salivary omentin-1 in healthy (H) and chronic periodontitis (CP) patients. Mater… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 34 publications
0
4
0
Order By: Relevance
“…28 Another recent study found that omentin-1 expression was low in patients with periodontitis. 29 Our results demonstrated that treatment with biological AMP periodontal gel led to lower levels of TNF-α and IL-6 compared with those without receiving the treatment, while omentin-1 levels were significantly higher (p < 0.05). This suggested that the gel could effectively reduce inflammatory factor levels among periodontitis patients.…”
Section: Discussionmentioning
confidence: 50%
See 1 more Smart Citation
“…28 Another recent study found that omentin-1 expression was low in patients with periodontitis. 29 Our results demonstrated that treatment with biological AMP periodontal gel led to lower levels of TNF-α and IL-6 compared with those without receiving the treatment, while omentin-1 levels were significantly higher (p < 0.05). This suggested that the gel could effectively reduce inflammatory factor levels among periodontitis patients.…”
Section: Discussionmentioning
confidence: 50%
“…Previous research has demonstrated that chronic periodontitis can result in the release of inflammatory factors such as TNF‐α, resulting in the damage of alveolar bone 28 . Another recent study found that omentin‐1 expression was low in patients with periodontitis 29 . Our results demonstrated that treatment with biological AMP periodontal gel led to lower levels of TNF‐α and IL‐6 compared with those without receiving the treatment, while omentin‐1 levels were significantly higher ( p < 0.05).…”
Section: Discussionmentioning
confidence: 99%
“…NSAIDs can cause ulcers and bleeding in the gastric tract. Studies in the USA found that about 16,000 people die from gastrointestinal side effects [39][40][41][42][43][44][45][46][47].…”
Section: Discussionmentioning
confidence: 99%
“…57,58 An association between reduced salivary omentin-1 levels and increased periodontal parameters was found in patients with chronic periodontitis. [59][60][61] Additionally, higher salivary omentin-1 levels after nonsurgical periodontal therapy were also concomitant with an improvement in the patient's periodontal health status. [59][60][61] Finally, Figure 2 and Table 1 show some of the main pro-and anti-inflammatory actions of the different adipokines contributing to periodontitis.…”
Section: Adipokine Role Mechanism Of Action Highlightsmentioning
confidence: 99%
“…[59][60][61] Additionally, higher salivary omentin-1 levels after nonsurgical periodontal therapy were also concomitant with an improvement in the patient's periodontal health status. [59][60][61] Finally, Figure 2 and Table 1 show some of the main pro-and anti-inflammatory actions of the different adipokines contributing to periodontitis.…”
Section: Adipokine Role Mechanism Of Action Highlightsmentioning
confidence: 99%